2013
DOI: 10.1097/coh.0b013e328361cfff
|View full text |Cite
|
Sign up to set email alerts
|

Using nonhuman primates to model HIV transmission

Abstract: Purpose of Review One of the major obstacles in fully understanding HIV transmission comes from the impracticality of studying transmission in humans. Because of this encumbrance, the early phases of HIV transmission and systemic dissemination are poorly understood. In order to fully comprehend these critical steps in HIV infection, animal models must be devised to accurately reflect HIV’s mode of action. This review seeks to highlight the essential nature of modeling HIV transmission in nonhuman primates. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
0
25
1
Order By: Relevance
“…The high genetic diversity identified in these chronic samples confirmed our assumption that the association between seronegativity and high VLs is indeed due to recent infection. We therefore assessed in these samples the number of transmitted founder variants and showed that SIV transmission in the wild is characterized by the same bottleneck as the one described in progressive HIV/SIV infections (49,50,111).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high genetic diversity identified in these chronic samples confirmed our assumption that the association between seronegativity and high VLs is indeed due to recent infection. We therefore assessed in these samples the number of transmitted founder variants and showed that SIV transmission in the wild is characterized by the same bottleneck as the one described in progressive HIV/SIV infections (49,50,111).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in the vast majority of transmissions, infection is initiated by a single genetic unit (50). It is considered that this genetic bottleneck is due to either a very low infectious dose at the time of transmission, a significant host barrier to new infections, or both (49,50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limiting-dose SIV challenges, which involve a reduction of the experimental viral inoculum size such that systemic infection is initiated by either one or only a few transmitted viral variants, have become a common and preferred method of modeling mucosal HIV infection in NHPs (1,(10)(11)(12)(13). This approach, which more closely recapitulates the inefficient nature of mucosal HIV transmission than traditional "high-dose" challenge models, requires the use of a virus stock containing sufficient sequence diversity to allow individual viral variants to be distinguished.…”
Section: Discussionmentioning
confidence: 99%